Formalización municipal de micro y pequeñas empresas comerciales para generar su crecimiento y desarrollo económico local de Tayabamba – 2018 - Pérez Mattos, Edinson Silverio (2019)
The research is aimed at determining if the Municipal Policies for Local Growth and Development are achieved through the formalization of the municipal operating license of the Micro and Small Commercial Companies of Tayabamba - 2018. The descriptive method of character applied using the methods and techniques of interview, survey and documentary analysis was used, concluding that. Local economic development is directly related to compliance with the Organic Law of Municipalities, which establishes that each municipality is competent and responsible for the level of local development aimed at improving the image of the territory, promoting the formalization of new companies, consolidating and expanding existing, motivate their capacity for innovation to improve the well-being, employment and income of the population. It is concluded that MYPES development promotion policies have been planned, but are not regularly monitored; there being 48% informality; constituting a disadvantage since they cannot be subject to financing lines., The Provincial Municipality of Pataz - Tayabamba, in the period 2018 - 2019, has been formulating decisions to improve its policies towards local economic development. It is the responsibility of each municipality to lead and summon the living forces and institutions and the population to adopt coherent plans for development, situation that is not given due importance and is not attended to.